Visual Aesthetics of Transgression (KULT_online, 2010)
The edited volume Maßlose Bilder. Visuelle Ästhetik der Transgression (Immoderate Images. Visual Aesthetics of Transgression) introduces a concept of transgression as a critical device in order to question the aesthetic, ethical, and epistemological predicaments assigned to visual media. The attempt to transgress the confines of the visible and the ostensible is not only a major feature of modern art, but also a decisive constituent of an ethics of perception and a self-reflective image production, which also challenges a presupposition of scientific reliability. The contributors to this volume come from the fields of art theory, philosophy, theory of media, theatre, film, and architecture, as well as from the fields of astrophysics, mathematics, and physiology. The editors Ingeborg Reichle and Steffen Siegel are members of the interdisciplinary group Bildkulturen (Visual Cultures) at the Berlin-Brandenburg Academy of Science.